2020
DOI: 10.3389/fcell.2020.00107
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Derived Extracellular Vesicles in Aging

Abstract: Aging is associated with high prevalence of chronic degenerative diseases that take a large part of the increasing burden of morbidities in a growing demographic of elderly people. Aging is a complex process that involves cell autonomous and cell nonautonomous mechanisms where senescence plays an important role. Senescence is characterized by the loss of proliferative potential, resistance to cell death by apoptosis and expression of a senescence-associated secretory phenotype (SASP). SASP includes pro-inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 72 publications
0
60
0
Order By: Relevance
“…Conversely, confluent MSCs produce lower amounts of EVs than proliferating MSCs (Patel et al, 2017). The impact of senescence on the production and functionality of MSC-EVs in different therapeutic applications has recently been reviewed (Boulestreau et al, 2020). EVs from aging MSCs did not exhibit the protective effect of EVs from young MSCs in an acute lung injury model (Huang et al, 2019).…”
Section: Msc Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, confluent MSCs produce lower amounts of EVs than proliferating MSCs (Patel et al, 2017). The impact of senescence on the production and functionality of MSC-EVs in different therapeutic applications has recently been reviewed (Boulestreau et al, 2020). EVs from aging MSCs did not exhibit the protective effect of EVs from young MSCs in an acute lung injury model (Huang et al, 2019).…”
Section: Msc Sourcesmentioning
confidence: 99%
“…Importantly, although quality controls for cell production include cell viability and apoptosis rate measurements, they do not assess cell senescence. Yet, EV yield is higher when using senescent cells, and their cargo composition is altered (abnormal levels of some miRNAs) [for review, see Boulestreau et al (2020)]. The proportion of senescent cells in the production batches and their effect on EV content should be taken into account in quality control procedures.…”
Section: Conclusion: Challenges and Perspectivesmentioning
confidence: 99%
“…Recent studies report increasing proliferation induced by younger MSC-derived secretome, probably due to the secretion of rejuvenating growth factors such as GDF11 [190,191]. Interestingly, other studies have suggested that the secretome of senescent MSCs has a biological effect on their microenvironment [103,189,192,193]. This senescence messaging secretome, or senescence-associated secretory phenotype (SASP), probably induces changes in the cellular transcriptional program [194] which, in turn, lead to changes in the number and composition of EVs, thus reflecting the senescent profile of the parent MSCs [192,193,195].…”
Section: Large Scale Production Of Exosomesmentioning
confidence: 99%
“…Interestingly, other studies have suggested that the secretome of senescent MSCs has a biological effect on their microenvironment [103,189,192,193]. This senescence messaging secretome, or senescence-associated secretory phenotype (SASP), probably induces changes in the cellular transcriptional program [194] which, in turn, lead to changes in the number and composition of EVs, thus reflecting the senescent profile of the parent MSCs [192,193,195]. SASPs have also been reported to play an effective role in inducing senescence in immortalized prostate cells [193].…”
Section: Large Scale Production Of Exosomesmentioning
confidence: 99%
“…Moreover, we have enough scientific evidence that relates aging to the high prevalence of chronic degenerative diseases with increasing morbidity among the elderly [9]. It is well-known that aging is related to cell senescence, which compromises its proliferative potential and leads to the appearance of a specific secretory phenotype, which creates an unfavorable tissue microenvironment.…”
Section: Introductionmentioning
confidence: 99%